ANALISIS KESESUAIAN POLA RUANG RENCANA DETAIL TATA RUANG (RDTR) TERHADAP TINGKAT KERAWANAN BENCANA DI KAWASAN PERKOTAAN KAYU TANAM - Muhammad Andika Rachman; Ahyuni Ahyuni (JURNAL BUANA, 2025)
The Kayu Tanam Urban Area has various morphological variations, namely agricultural areas on the South side, hilly areas on the West side and mountainous areas on the North side. This situation gives rise to various potential natural disasters in the Kayu Tanam urban area, so it is necessary to check the suitability of the spatial pattern for the existing disaster vulnerability. This research uses quantitative descriptive methods, by carrying out overlay and scoring techniques on flood parameters based on Paimin (2009) and overlaying landslide parameters which is carried out to determine the vulnerability class of the classification results of each parameter which can cause low, medium and high landslide categories to occur. The results of this research show that the percentage of area prone to landslides is dominated by the Type C Low Landslide Susceptibility Zone, 2328.66 ha, while the least vulnerable area is the Type A High Landslide Susceptibility Zone, 11.19 ha. Then the percentage area prone to flooding in the Not Prone class is 3057.68 ha, Slightly Prone 956.24 ha, Somewhat Prone 37.96 ha and Prone 99.17 ha.